Pengaruh Model Pembelajaran Studi Kasus terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran Fikih Fase F - Ceceng Ceceng; Mala Nurol Awwaliyyah (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
Critical thinking is an essential skill that students must possess to analyze, evaluate, and solve problems logically and systematically. However, many students still demonstrate weaknesses in this skill. One effective solution is the implementation of a case study learning model, which actively engages students in analyzing real-life problems, evaluating arguments, and finding evidence-based solutions. This approach not only facilitates theoretical understanding of concepts but also trains students to think critically in dealing with complex situations, making learning more meaningful and relevant. This study aims to describe: (1) the application of the case study learning model in Phase F of Islamic Jurisprudence (Fiqh), (2) students’ critical thinking skills, and (3) the effect of the application of the case study learning model on students’ critical thinking skills. The study used a descriptive quantitative method with data collection techniques through observation, documentation studies, and questionnaires on 36 students. The analysis results showed an average application of the case study learning model of 4.58 in the “Very Good” category and a critical thinking ability of 4.16 in the “Very Good” category. Statistical tests show that there is an influence of the application of the case study learning model on critical thinking skills of 51.4%, while 48.6% is influenced by other factors. Keywords: critical thinking, case study learning model, fikih subject